2012
DOI: 10.4137/bmi.s8703
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Effects of Matrix Interference in the Measurement of Urine Protein Analytes

Abstract: Using multiplex bead assays to measure urine proteins has a great potential for biomarker discovery, but substances in urine (the matrix) can interfere with assay measurements. By comparing the recovery of urine spiked with known quantities of several common analytes, this study demonstrated that the urine matrix variably interfered with the accurate measurement of low abundance proteins. Dilution of the urine permitted a more accurate measure of these proteins, equivalent to the standard dilution technique wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…In contrast to the sensor previously reported [100], the optimized assay was able to detect endogenous DA or UA in un-diluted serum samples. But some literature has suggested that larger peaks which displayed higher DA or UA concentrations were not linear in the whole sample without or less dilution [99,[101][102]. These reported suggested that interference due to serum complicated composition (especially ascorbic acid) was proportionally higher for less diluted samples, which was in accordance with the results described by other authors.…”
Section: Page 21 Of 72supporting
confidence: 91%
“…In contrast to the sensor previously reported [100], the optimized assay was able to detect endogenous DA or UA in un-diluted serum samples. But some literature has suggested that larger peaks which displayed higher DA or UA concentrations were not linear in the whole sample without or less dilution [99,[101][102]. These reported suggested that interference due to serum complicated composition (especially ascorbic acid) was proportionally higher for less diluted samples, which was in accordance with the results described by other authors.…”
Section: Page 21 Of 72supporting
confidence: 91%
“…Urine was diluted 1∶10 to reduce interference from the urine matrix [16]. Measurements were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…For urine, a diluent of phosphate buffered saline is recommended for use; however this does not resolve the issue of variability of urine matrix components as the measurements appear less stable compared to those in serum and plasma. [ 28 ] To our knowledge the only urinary protein measured by ELISA in clinical laboratories is albumin. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…High variability was observed in protein recovery in the urine samples even between assays indicating that matrix components differ among urine samples and also highlighting their ability to variably interfere in accurate protein measurement. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%